Adsorption of patent blue V from textile industry wastewater using sterculia alata fruit shell biochar: Evaluation of efficiency and mechanisms - Giri, B.S.; Goswami, M.; Kumar, P.; Yadav, R.; Sharma, N.; Sonwani, R.K.; Yadav, S.; Singh, R.P.; Rene, E.R.; Chaturvedi, P.; Singh, R.S. (MDPI AG, 2020)
Biochar prepared from Sterculia alata fruit shell showed a better performance for dye removal than the biomass from Sterculia alata fruit shell. The important process parameters-namely the pH, the amount of biochar, the initial dye concentration and the contact time-were optimized in order to maximize dye removal using biochar of Sterculia alata fruit shell as the bio-sorbent. The results from this study showed that the maximum adsorption of dye on the biochar was obtained at a biochar dosage of 40 g/L, at a contact time of 5 h, and an initial dye concentration of 500 mg/L (pH 2.0; temperature 30 ± 5 °C). The increase in the rate adsorption with temperature and the scanning electron microscopic (SEM) images indicated the possibility of multilayer type adsorption which was confirmed by better fit of the Freundlich adsorption isotherm with the experimental data as compared to the Langmuir isotherm. The values n and R2 in the Freundlich isotherm were found to be 4.55 and 0.97, respectively. The maximum adsorption capacity was found to be 11.36 mg/g. The value of n > 1 indicated physical nature of the adsorption process. The first and second order kinetics were tested, and it was observed that the adsorption process followed the first-order kinetics (R2 = 0.911). © 2020 by the author.
Keywords: Patent Blue V; Langmuir isotherm; Freundlich isotherm; SEM; removal efficiency